2016
DOI: 10.1016/j.drugalcdep.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mortality and physiologic injury evident with lower alcohol exposure among HIV infected compared with uninfected men

Abstract: Background HIV infected (HIV+) individuals may be more susceptible to alcohol-related harm than uninfected individuals. Methods We analyzed data on HIV+ and uninfected individuals in the Veterans Aging Cohort Study (VACS) with an Alcohol Use Disorders Identification Test-Consumption AUDIT-C score from 2008–2012. We used Cox proportional hazards models to examine the association between alcohol exposure and mortality through July, 2014; and linear regression models to assess the association between alcohol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
150
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 55 publications
5
150
1
1
Order By: Relevance
“…Nevertheless, results of this study were in agreement with the overall association found. It should be noted that, although not included in our meta-analysis because it was a cohort with a severe disease, Justice et al 22 showed that among US Veterans, the risk curve for all-cause mortality predicted by the AUDIT-C was much steeper among patients with HIV compared with non-HIV-positive Veterans.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, results of this study were in agreement with the overall association found. It should be noted that, although not included in our meta-analysis because it was a cohort with a severe disease, Justice et al 22 showed that among US Veterans, the risk curve for all-cause mortality predicted by the AUDIT-C was much steeper among patients with HIV compared with non-HIV-positive Veterans.…”
Section: Discussionmentioning
confidence: 96%
“…Alcohol use is also associated with ART non-adherence and preventable mortality among PLWH (Braithwaite & Bryant, 2010). Even modest alcohol use has adverse impacts on HIV-related health outcomes independent of ART adherence (Justice et al, 2016). Likewise, drinking increases the risk of developing diabetes in persons with comorbid hypercholesterolemia (i.e., elevated levels of cholesterol) (Holbrook et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to older age, HIV-associated inflammation, frailty, and substance use (i.e. tobacco, alcohol, and other drugs) (Justice et al, 2016; Crothers et al, 2005; Brothers & Rockwood, 2014) contribute to a greater number of comorbidities complicating the management of HIV infection. Treatment guidelines, developed for people with one disease, but applied to people with multiple chronic conditions can lead to the prescription of multiple concomitant medications, often termed “polypharmacy,” resulting in a significant daily medication burden (Edelman et al, 2013; Moore, Mao, & Oramasionwu, 2015).…”
Section: Introductionmentioning
confidence: 99%